COPD characteristics and socioeconomic burden in Hellenic correctional institutions - Bania, Eleni G (Int J Chron Obstruct Pulmon Dis, 2016)
BACKGROUND: The high prevalence of smoking (80%) in Greek correctional institutions is anticipated to result in high prevalence of COPD in such settings. AIM: The aim of the Greek obstructive luNg disease epidemiOlogy and health economics Study In corrective institutionS (GNOSIS) is to determine the prevalence of smoking and COPD among inmates and to assess the health-related quality of life. METHODS: GNOSIS, a cross-sectional epidemiological study, was conducted between March 2011 and December 2011 in seven correctional institutions in Greece. RESULTS: A total of 552 participants, 91.3% male, median age of 43.0 years (interquartile range: 35–53), were enrolled. COPD prevalence was 6.0% and was found to increase with age (18.6% among those ≥60 years), length of prison stay, and length of sentence. Of the participants diagnosed with COPD, 36.4% were diagnosed with Global initiative for chronic Obstructive Lung Disease (GOLD) stage I and 51.5% were diagnosed with stage II. Dyspnea severity was assessed as grades 0–1 on the medical research council dyspnea scale for 88.3%, while 31% reported ≥2 COPD exacerbations in the past year. Seventy-nine percent of the total number of the participants were smokers, with a median smoking of 20.0 cigarettes per day, while 42.9% were assessed as having a strong addiction to nicotine. The median EuroQol visual analog scale score was 70.0 (interquartile range: 60.0–90.0). Problems in the dimension of anxiety/depression were reported by 82.8%. CONCLUSION: The results of the study support the notion that the prevalence of COPD among inmates of Greek correctional institutions may increase in the following years. The findings underscore the importance of taking actions to limit COPD prevalence and its risk factors in the Greek correctional system.